An Assessment of Pollution with Polychlorinated Dibenzodioxins (PCDDs) and Polychlorinated Dibenzofuranes (PCDFs) at Steelmaking. (2016) - Ilutiu-Varvara, Dana-Adriana
Abstract: Polychlorinated dibenzodioxins (PCDDs) and polychlorinated dibenzofuranes (PCDFs) are types of persistent organic pollutants (POPs) with a wide range of toxic responses and carcinogenic properties. These pollutants have a negative impact on the steelworkers, environment and population. The aim of this paper is to assess the polychlorinated dibenzodioxins and polychlorinated dibenzofuranes emissions from steelmaking in the electric arc furnace in order to improve the gaseous emissions management. The analyses of polychlorinated dibenzodioxins and polychlorinated dibenzofuranes was performed using a high resolution gas chromatograph/high resolution mass spectrometer (HRGC/HRMS). After evaluating the pollution levels of polychlorinated dibenzodioxins and dibenzofuranes during steelmaking it results that: the total PCDDs and PCDFs concentrations in the stack flue gases was 0.9886 ng/Nm 3 ; in the composition of flue gases predominates the following compounds: tetrachloro dibenzofuran (TCDF) 40.55%, pentachloro dibenzofuran (PeCDF) 19.4%, tetrachloro dibenzo-p-dioxin (TCDD) 12.5%, pentachloro dibenzo-p-dioxin (PeCDD) 10.7% and hexachloro dibenzofuran (HxCDF) 10.5%; the calculated total value of Toxic Equivalent Quantity (Total TEQ) is 0.326482 ng I-TEQ/Nm 3 ; the level of PCDD and PCDF concentrations depends on the plastic (such as polyvinylchloride) content of material input. The reduction of pollution with polychlorinated dibenzodioxins and dibenzofuranes to the steelmaking in the electric arc furnace is possible by charge component selection and by the use of raw materials with reduced plastics content.